Cooperative interactions between seed-borne bacterial and air-borne fungal pathogens on rice - Boknam Jung (Nature Portfolio, 2018)
Interactions between bacteria and fungi are common and contribute to ecosystem processes. Here, Jung et al. show that the interaction between two plant pathogens (a seed-borne bacterium and an air-borne fungus) promotes their own survival and dispersal, as well as disease progression on rice plants.